Evolution of gastric ulcer surgery - Suiffet, Walter (Cirugía del Uruguay, 1982)
The author analyzes the evolution of the gastric ulcer surgery along one century. Rydiguier performed the first gastrectomy because of gastric ulcer en 1881. He was successful and he went on performing it in spite of the difficulties of the time. The use of vagotomy has been greatly questioned and experience does not seem to be favorable, considering the unequal results. It is considered that the G U surgery requires, as a fundamental element, the exeresis of the lesion and a wide resection of the lesser curvature and a correct resection of the area where there are lesions of the gastric mucosa that tend to the appearance of the gastric ulcer. There is no reason for a resection of more than 40% of the stomach- except in the cases of acid hypersecretion. In case of risk of general arder, more conservative tactics may be used. Tactics must be adjusted to the topography of the lesion and the secretorial activity of each case. Tactics of high and juxtacardial GU are not analyzed. Mortality and relapse rates are analyzed.